2021
DOI: 10.3389/fonc.2021.660805
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Ultrasound-Assisted Extent of Resection Assessment in Pediatric Neurosurgical Oncology

Abstract: Central nervous system tumors represent the most frequent solid malignancy in the pediatric population. Maximal safe surgical resection is a mainstay of treatment, with significant prognostic impact for the majority of histotypes. Intraoperative ultrasound (ioUS) is a widely available tool in neurosurgery to assist in intracerebral disease resection. Despite technical caveats, preliminary experiences suggest a satisfactory predictive ability, when compared to magnetic resonance imaging (MRI) studies. Most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…As this data emphasizes the impact of resection extent and residual tumor volume in pediatric low-grade glioma surgery, it subsequently highlights the importance of preoperative risk assessment and the role of technical modalities for intraoperative resection control including intraoperative ultrasound, high-field intraoperative MRI (iMRI) and electro-physiological intraoperative neuromonitoring (IOM), as some of these modalities have shown to play a crucial role in maximizing resection extent while preventing irreversible long-term neurologic impairment [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As this data emphasizes the impact of resection extent and residual tumor volume in pediatric low-grade glioma surgery, it subsequently highlights the importance of preoperative risk assessment and the role of technical modalities for intraoperative resection control including intraoperative ultrasound, high-field intraoperative MRI (iMRI) and electro-physiological intraoperative neuromonitoring (IOM), as some of these modalities have shown to play a crucial role in maximizing resection extent while preventing irreversible long-term neurologic impairment [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exoscope appears to be well-suited to be integrated with the use of intraoperative ultrasound, a technology that has proved useful in settings, such as adult ( 14 ) and pediatric ( 15 ) brains and spine ( 16 ) surgery. Bulky operative microscope heads often need to be removed from the operative field to apply the ultrasound probe to the tissue, while smaller exoscope cameras, which can sit further away from the operative field, allow for use of ultrasound probe without their removal and, indeed, even with picture-in-picture visualization of the ultrasound images on the exoscope screen ( 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…In some complicated cases, intraoperative ultrasound and MRI were applied to assess the extent of resection. Carai et al (34) revealed that intraoperative ultrasound had a very good predictive value in neurosurgery to assist in intracerebral disease resection and improved the assessment ability of surgical resection (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Carai et al. ( 34 ) revealed that intraoperative ultrasound had a very good predictive value in neurosurgery to assist in intracerebral disease resection and improved the assessment ability of surgical resection ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%